Spectral analysis of flavonoids content of dandelion Taraxacum officinale W. and chicory usual Cichorium intybus L. depending on growing places - Довгопола, К. А. (Problems of Environmental Biotechnology, 2017)
Article presents results of the identification of flavonoids by chromatographic method, dependence of content flavonoids on conditions of plant growth. Coefficients of technogenic concentrations of heavy metals in soil samples and intensity of migration of pollutants from soil to plants using biological absorption coefficient were established.